Digitally-disadvantaged languages - Isabelle A. Zaugg; Anushah Hossain; Brendan Molloy (Internet Policy Review, 2022)
Digitally-disadvantaged languages face multiple inequities in the digital sphere including gaps in digital support that obstruct access for speakers, poorly-designed digital tools that negatively affect the integrity of languages and writing systems, and unique vulnerabilities to surveillance harms for speaker communities. This term captures the acutely uneven digital playing field for speakers of the world's 7000+ languages.
Keywords: 300; Digital discourse; Language; Social justice; Surveillance